Clinical Characteristics of Vegetative Manifestations in Young Children with Acute Pneumonia - Abdurakhmonov, Zhasur Ne’matovich; Sharipova, Oliya Askarovna; Sherzod, Bakhronov Samievich (Indonesian Journal Publisher, 2024)
60 sick children with acute pneumonia aged from 1 to 3 years were examined. The control group consisted of 30 healthy children of the same age. The experience of the clinic has shown that all children with acute pneumonia have disorders of the autonomic nervous system, which aggravates the course of this disease. The author found that children with acute pneumonia showed characteristic changes in autonomic regulation, manifested by a predominance of hypersympathicotonic initial autonomic tone, which generally indicates a state of overstrain of the body's adaptive capabilities. High tension and disruption of adaptation increase the risk of an unfavorable outcome of the disease. In patients with acute pneumonia who received vegetotropic drugs and a multivitamin complex as part of complex therapy, more pronounced positive dynamics in indicators of autonomic homeostasis were noted.